Maintenance of Cement Concrete Pavements: Defects and Their Elimination - Urolova , Khadicha; Urokov, Aslidin (Universitas Muhammadiyah Sidoarjo, 2025)
The main purpose of this article is to analyze the operational condition of existing cement-concrete roads in the Republic of Uzbekistan and identify work to eliminate existing problems. According to this, defects in cement concrete pavements, using the method of visual examination of the condition proposed by British specialists, are the objects of study of the section of the A-380 “Guzor-Bukhara-Nukus-Beynov” highway (480-490 km) and section of the M-39 “Almaty-Bishkek-Tashkent-Shakhrisabz-Termiz” highway (1173-1184 km). Based on the results, coating surface defects and structural defects were classified, and the causes and consequences of their occurrence were analyzed. The importance of improving storage technologies in eliminating problems caused by defects in cement concrete pavements is emphasized, and through this, issues of increasing the service life of coatings are considered. At the same time, recommendations were made on continuous monitoring of the condition of the roads in use, organization, and planning of operational works based on the results of the study of the pavement condition. Highlights: Analysis of Road Conditions: Evaluating defects in Uzbekistan’s cement-concrete highways. Causes and Solutions: Identifying defects, their causes, and solutions for longevity. Recommendations: Continuous monitoring, improved storage, and operational planning for Keywords - cement concrete, service life, surface defects, structural defects, Visual condition surveys (VCS).